Pemberdayaan UMKM Pempek Kiyya Melalui Penguatan Media Promosi dan Pengembangan Identitas Usaha - Dicky Ramadani; Nicolas Aldy Syahputra; Fikri Amrillah; Via Wahyuningtyas; Allysia Safira Putri Palevy; Santoso Santoso (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of the Indonesian economy which have a strategic role in national economic development. In the context of the traditional culinary industry, pempek as one of Palembang's typical foods has great economic potential. This traditional food has become a superior commodity that is not only popular in its area of ​​origin, but has also spread to various regions in Indonesia. In this Real Work Lecture (KKN), the activity began with field observation methods, in-depth interviews, and FGD (Focus Group Discussion) aimed at discussing the concept of developing promotional media and business identity together with business owners in order to identify the main problems faced, especially in terms of promotional media and business identity. The main problem faced is the limitations in marketing and branding aspects, especially in terms of effective promotional media such as banners, TikTok content, business cards and strong business identities such as business plaques and websites. Through the right approach, it aims to increase business visibility, expand market reach, and ultimately increase sales turnover. The mentoring program has succeeded in increasing the managerial capabilities of MSME owners in managing modern marketing aspects. Training in the use of digital platforms such as Instagram, Tiktok and WhatsApp Business has equipped business actors with practical skills in creating attractive visual content and strategic publication scheduling. changing the business approach from being conventional to being more professional and systematic.